2013
DOI: 10.1267/ahc.13003
|View full text |Cite
|
Sign up to set email alerts
|

Nerve Growth Factor Involves Mutual Interaction between Neurons and Satellite Glial Cells in the Rat Trigeminal Ganglion

Abstract: Nerve growth factor (NGF) plays a critical role in the trigeminal ganglion (TG) following peripheral nerve damage in the oral region. Although neurons in the TG are surrounded by satellite glial cells (SGCs) that passively support neural function, little is known regarding NGF expression and its interactions with TG neurons and SGCs. This study was performed to examine the expression of NGF in TG neurons and SGCs with nerve damage by experimental tooth movement. An elastic band was inserted between the first a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 23 publications
1
15
0
Order By: Relevance
“…The small increase of NGF in the DG tissue ( Fig. 7a/c) could also impact on these phenomena [49,[51][52][53]. Nevertheless, although proteomic studies are still scarce to explain the functional effects of MSCs secretome (including that of HUCPVCs as well), previous studies from our group have revealed, through the use of targeted and non-targeted proteomic-based techniques, the presence of important molecules for CNS physiology, within it [33,37].…”
Section: Discussionmentioning
confidence: 92%
“…The small increase of NGF in the DG tissue ( Fig. 7a/c) could also impact on these phenomena [49,[51][52][53]. Nevertheless, although proteomic studies are still scarce to explain the functional effects of MSCs secretome (including that of HUCPVCs as well), previous studies from our group have revealed, through the use of targeted and non-targeted proteomic-based techniques, the presence of important molecules for CNS physiology, within it [33,37].…”
Section: Discussionmentioning
confidence: 92%
“…In agreement with these studies, our present findings suggest that the preservation of the size of neuronal soma promoted by estrogens requires the activation (stronger GFAP-ir) and, likely, proliferation of the SGC, as well as an increase in the GDNF expression. Indeed, the SGC could favor the overexpression or post-processing of the GDNF as reported for other neurotrophic factors [48, 49]. Remarkably, the SGCs express ER ability to modulate the expression of several genes as a response of E2 treatment [50].…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, pregnancy has a clear impact on the size of neuronal somata of paravaginal ganglia in rabbits [7] as compared to that of the vaginal distention achieved in non-cycled female rats [55]. Taking into account that the organization of SGC changes along lifespan [29, 45] and its trophic involvement in the neuronal morphology [48, 49], our present study highlights a plausible contribution of the SGC in the estrogen-related plasticity of the somata size of paravaginal neurons. Further experiments should determine particular associated processes (i.e., variations in neuronal metabolism, synaptic and/or dendritic organization, profile of neurotransmitters and neuromodulators, and expression of markers of glial activity).…”
Section: Discussionmentioning
confidence: 99%
“…There is increasing evidence that NTs are peripheral pain mediators and involved in different pain states (Khan & Smith, ). NTs are expressed in both neurons and SGCs of the TG (Kurata et al, , Quartu, Geic, & Fiacco, , Wetmore & Olson, ). There are two classes of receptors for neurotrophins: p75 and the Tyrosine kinase (Trk) receptors, which are detected in the TG neurons (Gaspersic, Kovacic, Cor, & Skaleric, ; Wetmore & Olson, ).…”
Section: Crosstalk Between Sgcs and Neuronsmentioning
confidence: 99%
“…There are two classes of receptors for neurotrophins: p75 and the Tyrosine kinase (Trk) receptors, which are detected in the TG neurons (Gaspersic, Kovacic, Cor, & Skaleric, ; Wetmore & Olson, ). Kurata's study demonstrates that NGF‐immunoreactive SGCs increase significantly following peripheral nerve damage in the oral region, and increased NGF may be involved in the restoration of damaged neurons (Kurata et al, ). In addition, NGF depletion inhibits injury‐induced SGC responses after inferior alveolar nerve injury (Anderson et al, ).…”
Section: Crosstalk Between Sgcs and Neuronsmentioning
confidence: 99%